O subsídio Recordando e Renovando da rede municipal de São Bernardo do Campo (1982-1995): análise material de um impresso de formação e normatização das práticas docentes na escola para a infância - Leibruder, Marly (2007)
This paper goals to study the pedagogical journal Recordando e Renovando (Reminding and Renewing), published between 1982 and 1995 to the Municipal Public Schools of São Bernardo do Campo, considering it as an object of investigation and a historiography information issue that was used to intermediate the relations between teachers and the pedagogical references to be implemented or kept. The research had as start the proposal to consider the printed text as a cultural object that keeps its production and uses characteristics (Certeau, 1994; Chartier, 1990; Carvalho & Hansen, 1996; Toledo, 2001), what means that it is supposed to work with its contents in respect of the production, the circulation and the appropriation processes made by their agents and addressees. The central hypothesis is that the printed text brings in its materiality different representations of children, early childhood education and reader teacher to whom it is addressed. During the methodological construction, we had tried to describe the material faces of the pedagogical journal, periodizing it according to its rhythms of production, the coordination changes, and the participation or changes of the reading public, as well as the indication of reading as a part of an editorial project to keep or change the educational practices. As a result, it was possible to identify three established periods during the publication life, from the centrality of the childhood and emphasis on didactic models (1982-1987) to the dilution of the children representation among new educational and consumerists issues (1993-1995) after get across a period of serious questioning in which the children are represented as a subject of rights and as a constructor of his knowledge (1989-1992)